Finite element analysis to simulate the effect of impact rollers for estimating the influence depth of soil compaction - Kim, Kukjoo; Chun, Sanghyun (KSCE journal of civil engineering, 2016)
The use of impact rollers has increased for many decades due to its diverse advantages. However, the current lack of theoretical verification and research-based technical guidelines that can effectively describe the effect of impact rollers is probably the greatest deficiency in our ability to accurately predict the benefits of deep compaction provided by impact compaction rollers. The 3-D Finite Element Analysis (FEA) was conducted using LS-DYNA to simulate the depth of influence for various impact rollers. Results indicated that the width of the contact area between the drum and the soil primarily controls the depth of compaction. The softer the soil is, the deeper the roller sinks in the soil. Also, the wider the contact area is, the deeper the compaction depth is. Thereby, the depth of compaction is highly dependent upon the stiffness of the soil. It was found that the surface pressure controls the degree of compaction and the surface pressure of the impact rollers is higher than that of the cylindrical rollers due to the dynamic effect. However, the distribution of the pressure is significantly variable for the impact rollers than the cylindrical rollers. It was concluded that the impact rollers seem to have more potential for use in final compaction of thicker layers.